Novel Approaches in Clinical Simulation: Immersive Educational Technology to Enhance Nursing Education - Oyekunle, David; Ugochukwu, Okwudili Matthew; Rosa, Renata Lopez; Rodriguez, Demostenes Zegarra; Fatai, Lateef Olawale (INFOCOMP Journal of Computer Science, 2024)
The emergence of virtual reality (VR) simulation has brought about a significant shift in the healthcare industry, as it integrates modern technologies with human talents to foster patient-centered care, clinical efficiency, and a compassionate healthcare digital ecosystem. The use of clinical simulation in nursing education has become essential in the current day, revolutionizing the training of future medical professionals. This paper explored the realm of simulation-based learning, illuminating its importance, obstacles, and endless potential in the field of nursing education. Given the ever-changing healthcare landscape, nurses need to possess a broad range of skills and a thorough comprehension of real-world situations. But conventional didactic methods frequently fail to adequately prepare student-nurses for the intricacies of clinical practice. VR is one of the most crucial elements of immersive learning that increases constructive pedagogic engagements due to generative imagination it offers. By using VR headgear or goggles, student-nurses can fully submerge themselves in a customized digital world as if they were truly there, interacting with their surroundings and learn in an interactive and pedagogic informative digital ecosystem. In order to help student-nurses practice problem-solving techniques without really placing themselves in risk, VR can also be used to construct very realistic simulations. In this study, the authors offered the transformative potential of VR, with significances to improve nursing education by offering engaging and interactive learning environments. The paper presented a novel approaches in addressing nursing education through technology familiarization, proposing a cutting-edge simulation platform using actor network (ANT) model for the resource distribution.